A surface modification method for cutting tools
By forming three-layer coatings of TiN, TiSiErN and ZrAlCuN on the surface of the cutting tool, combined with dry and wet micro-sand blasting treatment, the problem of insufficient bonding between the multi-coats and high surface roughness is solved, and the use of the tool is significantly improved Lifespan and performance.
Patent Information
- Application Number
- CN202211102927.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-09-09
AI Technical Summary
The multi-coat bonds of existing cutting tools are not tightly integrated, with large surface roughness and poor gloss, resulting in reduced service life and service performance.
Using a combination technology of three-layer coatings of TiN, TiSiErN and ZrAlCuN, TiN and TiSiErN coatings are deposited through multi-arc ion coating equipment, and ZrAlCuN coatings are deposited in magnetron sputtering equipment after dry microsand blasting treatment, combined with dry and wet micro-sand blasting treatment to improve the roughness and gloss of the coating surface.
It significantly improves the bonding strength between the coating and the tool matrix, improves surface roughness and gloss, extends the tool's service life, and improves its hardness and wear resistance.
Smart Images

Figure BDA0003841399770000071 
Figure HDA0003841399780000011 
Figure HDA0003841399780000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface treatment, and in particular to a surface modification method for a cutting tool. Background Art
[0002] The surface coating of the tool plays a key role in improving the tool performance and the advancement of cutting processing technology. It is an effective way to solve the tool wear resistance, toughness, heat resistance, anti-adhesion and other properties. Coated cutting tools have become an important symbol of modern tools.
[0003] As traditional tool materials, high-speed steel or carbide steel is increasingly unable to meet the development needs of the modern mechanical processing industry. Therefore, tool surface coating technology has emerged. Tool surface coating technology is a material surface treatment technology developed in recent decades. Under appropriate process and technical conditions, the coating has good properties. Coating it on the tool surface can greatly improve the service life of metal cutting tools. The current development trend of coatings is that coatings tend to be diversified and multi-layered. Multi-layer coatings can combine the advantages of single coatings. The emergence of multi-layer and multi-coatings and related technologies enables the coating to improve the bonding strength with the substrate and have the comprehensive performance of multiple materials, further improving the performance of the tool.
[0004] However, the existing multi-coatings after surface modification of cutting tools are not tightly bonded, the coating surface is rough and the glossiness is poor, which has an adverse effect on the surface of the coated tool, resulting in a reduction in performance such as service life and service performance. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a surface modification method for a cutting tool, forming a multi-coating of TiN coating, TiSiErN coating and ZrAlCuN coating on the surface of the cutting tool, thereby improving the bonding strength between the coating and the cutting tool, and effectively solving the problems of loose bonding between multiple coatings, large surface roughness and poor overall performance in the prior art.
[0006] The technical solution of the present invention to solve the above technical problem is as follows: a surface modification method of a cutting tool is provided, which comprises the following steps in sequence:
[0007] S1, depositing a TiN coating on the surface of the cleaned tool substrate by a multi-arc ion plating device;
[0008] S2, depositing a TiSiErN coating on the TiN coating;
[0009] S3. After the TiSiErN coating is subjected to dry micro-sandblasting treatment, a mixed gas of argon and nitrogen is introduced into the magnetron sputtering equipment to a vacuum degree of 0.6-0.8 Pa, the ZrAlCu alloy target is turned on, the ZrAlCuN coating is deposited, and the coating is taken out after cooling to room temperature, and wet micro-sandblasting treatment is performed to complete the surface modification of the cutting tool.
[0010] Further, in step S1, the specific steps of cleaning the tool substrate are:
[0011] S11, ultrasonically clean the tool substrate, rinse it with tap water and deionized water, then place it in 1wt% hydrochloric acid for activation for 2-3 minutes, rinse it with deionized water, place it in acetone for ultrasonic cleaning for 18-20 minutes, and dry it;
[0012] S12, placing the dried tool substrate under vacuum conditions and heating it to 200-400° C., introducing argon gas until the vacuum degree is 1-2 Pa, turning on the bias power supply to 1000-1200 V, and performing argon ion sputtering cleaning;
[0013] S13. After the tool substrate is cleaned by argon ion sputtering, argon gas is introduced again until the vacuum degree is 0.4-0.7 Pa, the power is 350-400 W, and the ion source is turned on for cleaning for 10-20 minutes to obtain the cleaned tool substrate.
[0014] The tool base material is titanium alloy Ti6Al4V, high speed steel or other cemented carbide.
[0015] Furthermore, in step S1, when depositing the TiN coating, the pressure is 2-4 Pa, the nitrogen flow rate is 80-100 mL / min, and the arc current is 100-120 A.
[0016] Furthermore, in step S2, when depositing the TiSiErN coating, a SiTi target containing 0.5-3wt% Er is used, the mass ratio of Si to Ti is 1:4, the pressure is 2-4Pa, the nitrogen flow rate is 80-100mL / min, and the arc current is 100-120A.
[0017] Furthermore, in step S3, during the dry micro-sandblasting treatment, irregular white corundum with a particle size of 20-40 μm is used for micro-sandblasting for 2-8 seconds by compressed air, and the micro-sandblasting pressure is 0.1-0.3 MPa.
[0018] Further, in step S3, when depositing the ZrAlCuN coating, the pulse voltage is 200-600V, the pulse frequency is 100-300Hz, the negative bias voltage is 300-400V, the ion source power is 200-300W, and the deposition time is 1-2h.
[0019] Furthermore, in step S3, during the wet micro-sandblasting treatment, spherical white corundum with a particle size of 20-40 μm is mixed with water and micro-sandblasted for 4-6 seconds, and the micro-sandblasting pressure is 0.2-0.4 MPa.
[0020] Furthermore, the thickness of the TiN coating is 0.2-0.4 μm, the thickness of the TiSiErN coating is 0.5-0.9 μm, and the thickness of the ZrAlCuN coating is 1-1.8 μm.
[0021] Furthermore, in the ZrAlCu alloy target, the Al atomic percentage does not exceed 15%, and the Cu atomic percentage does not exceed 2%.
[0022] Further, in step S3, the nitrogen partial pressure in the mixed gas is 0.01-0.1 Pa.
[0023] The present invention has the following beneficial effects:
[0024] 1. The present invention forms a multi-coating of TiN coating, TiSiErN coating and ZrAlCuN coating on the surface of the cutting tool, thereby improving the bonding strength between the coating and the cutting tool, and the surface roughness is small, the glossiness is good, and the service life of the tool can be extended. At the same time, its mechanical properties such as hardness are improved, and the problems of loose bonding between multiple coatings, large surface roughness and poor comprehensive performance in the prior art are effectively solved.
[0025] 2. The TiN coating of the present invention has good bonding force with the tool substrate, which can ensure the close bonding between the coating and the tool and improve the bonding strength; the Er element in the TiSiErN coating has the functions of refining grains, enhancing toughness and improving coating density, which can enhance the bonding strength between coatings and improve the overall performance and service life; the copper in the ZrAlCuN coating refines the nitride grains, and the formed grains are small and uniform, and its toughness is significantly improved, and it has the advantages of high hardness and good toughness, improves the ability to resist impact loads, and improves the overall hardness. The multilayer coating composed of the TiN coating, the TiSiErN coating and the ZrAlCuN coating combines the advantages of each coating, and while improving the bonding strength between the coating and the tool substrate and between the coatings, it also has high hardness and high toughness, significantly improves the service life of the cutting tool and reduces the processing cost.
[0026] 3. Dry micro-sandblasting was performed before depositing the ZrAlCuN coating. The irregular white corundum was carried by compressed air and impacted on the previously formed TiSiErN coating. The irregular edge angle had a certain cutting effect on the coating. While removing the pollutants on the coating surface, it also provided conditions for the deposition of the next coating. Under the action of the irregular edge angle, the coating surface would have irregular tiny pits (such as Figure 1), so the dry micro-sandblasting time should not be too long and the pressure should not be too high, otherwise it will increase the roughness of the coating surface. The above-mentioned tiny irregular pits will be more tightly combined when the ZrAlCuN coating is deposited, and the bonding strength is higher than that of the two coatings with smooth interfaces. After the ZrAlCuN coating is deposited, wet micro-sandblasting is performed again. The spherical white corundum impacts the coating surface under the action of water, which can effectively improve the roughness of the coating surface and make the surface smoother. The tiny spherical depressions make the light reflect on the coating surface to form a better glossiness ( Figure 2 ); Micro-sandblasting of the deposited ZrAlCuN coating will also improve its adhesion to the previously formed coating, improve the wear resistance and cutting performance of the tool, and significantly increase the tool life. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of dry micro-sandblasting;
[0028] Figure 2 Schematic diagram of wet micro-sandblasting. DETAILED DESCRIPTION
[0029] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0030] Embodiment 1:
[0031] A surface modification method for a cutting tool comprises the following steps in sequence:
[0032] S1. Deposit a 0.3 μm TiN coating on the surface of the cleaned high-speed steel tool substrate by a multi-arc ion plating device; the pressure is 2 Pa, the nitrogen flow rate is 80 mL / min, and the arc current is 100 A;
[0033] S2. Depositing a 0.8 μm TiSiErN coating on the TiN coating; using a SiTi target containing 0.5 wt% Er, a Si to Ti mass ratio of 1:4, a pressure of 2 Pa, a nitrogen flow rate of 80 mL / min, and an arc current of 100 A;
[0034] S3. The TiSiErN coating is subjected to dry micro-sandblasting treatment. Irregular white corundum with a particle size of 20 μm is used for micro-sandblasting by compressed air for 2 seconds. The micro-sandblasting pressure is 0.1 MPa. Then, a mixed gas of argon and nitrogen (nitrogen partial pressure is 0.01 Pa) is introduced into the magnetron sputtering equipment until the vacuum degree is 0.6 Pa. The ZrAlCu alloy target (Al atomic percentage 12%, Cu atomic percentage 1.5%) is turned on. The pulse voltage is 300 V, the pulse frequency is 100 Hz, the negative bias voltage is 300 V, the ion source power is 200 W, and the deposition is carried out for 1 hour. A 1.3 μm ZrAlCuN coating is deposited. After cooling to room temperature, it is taken out and subjected to wet micro-sandblasting treatment. Spherical white corundum with a particle size of 20 μm is used and mixed with water for micro-sandblasting for 4 seconds. The micro-sandblasting pressure is 0.2 MPa to complete the surface modification of the cutting tool.
[0035] Among them, in step S1, the specific steps of cleaning the tool substrate are:
[0036] S11, ultrasonically cleaning the tool substrate, then rinsing it with tap water and deionized water, then activating it in 1wt% hydrochloric acid for 2 minutes, rinsing it with deionized water, ultrasonically cleaning it in acetone for 18 minutes, and drying it;
[0037] S12, placing the dried tool substrate under vacuum conditions and heating it to 200° C., introducing argon gas until the vacuum degree is 1 Pa, turning on the bias power supply to 1000 V, and performing argon ion sputtering cleaning;
[0038] S13. After the tool substrate is cleaned by argon ion sputtering, argon gas is introduced again until the vacuum degree is 0.4 Pa, the power is 350 W, and the ion source is turned on for cleaning for 10 minutes to obtain the cleaned tool substrate.
[0039] Embodiment 2:
[0040] A surface modification method for a cutting tool comprises the following steps in sequence:
[0041] S1. Deposit a 0.2 μm TiN coating on the cleaned high-speed steel tool substrate using a multi-arc ion plating device; the pressure is 3 Pa, the nitrogen flow rate is 90 mL / min, and the arc current is 110 A;
[0042] S2. Depositing a 0.7 μm TiSiErN coating on the TiN coating; using a SiTi target containing 0.9 wt% Er, a Si to Ti mass ratio of 1:4, a pressure of 3 Pa, a nitrogen flow rate of 90 mL / min, and an arc current of 110 A;
[0043] S3. The TiSiErN coating was subjected to dry micro-sandblasting treatment. Irregular white corundum with a particle size of 30 μm was used for micro-sandblasting by compressed air for 5 seconds. The micro-sandblasting pressure was 0.2 MPa. Then, a mixed gas of argon and nitrogen (nitrogen partial pressure was 0.05 Pa) was introduced into the magnetron sputtering equipment until the vacuum degree was 0.7 Pa. The ZrAlCu alloy target (Al atomic percentage 12%, Cu atomic percentage 1.5%) was turned on. The pulse voltage was 400 V, the pulse frequency was 200 Hz, the negative bias voltage was 350 V, the ion source power was 250 W, the deposition was 1.5 hours, and a 1.5 μm ZrAlCuN coating was deposited. After cooling to room temperature, it was taken out and subjected to wet micro-sandblasting treatment. Spherical white corundum with a particle size of 30 μm was used and mixed with water for micro-sandblasting for 4 seconds. The micro-sandblasting pressure was 0.3 MPa to complete the surface modification of the cutting tool.
[0044] Among them, in step S1, the specific steps of cleaning the tool substrate are:
[0045] S11, ultrasonically clean the tool substrate, rinse it with tap water and deionized water, then place it in 1wt% hydrochloric acid for activation for 2 minutes, rinse it with deionized water, ultrasonically clean it in acetone for 19 minutes, and dry it;
[0046] S12, placing the dried tool substrate under vacuum conditions and heating it to 300° C., introducing argon gas until the vacuum degree is 1 Pa, turning on the bias power supply to 1100 V, and performing argon ion sputtering cleaning;
[0047] S13. After the tool substrate is cleaned by argon ion sputtering, argon gas is introduced again until the vacuum degree is 0.5 Pa, the power is 370 W, and the ion source is turned on for cleaning for 15 minutes to obtain the cleaned tool substrate.
[0048] Embodiment 3:
[0049] A surface modification method for a cutting tool comprises the following steps in sequence:
[0050] S1. Deposit a 0.4 μm TiN coating on the cleaned high-speed steel tool substrate surface by a multi-arc ion plating device; the pressure is 4 Pa, the nitrogen flow rate is 100 mL / min, and the arc current is 120 A;
[0051] S2. Depositing a 0.9 μm TiSiErN coating on the TiN coating; using a SiTi target containing 2 wt% Er, a Si to Ti mass ratio of 1:4, a pressure of 4 Pa, a nitrogen flow rate of 100 mL / min, and an arc current of 120 A;
[0052] S3. The TiSiErN coating is subjected to dry micro-sandblasting treatment. Irregular white corundum with a particle size of 40 μm is used for micro-sandblasting by compressed air for 7 seconds. The micro-sandblasting pressure is 0.3 MPa. Then, a mixed gas of argon and nitrogen (nitrogen partial pressure is 0.1 Pa) is introduced into the magnetron sputtering equipment until the vacuum degree is 0.8 Pa. The ZrAlCu alloy target (Al atomic percentage 12%, Cu atomic percentage 1.5%) is turned on. The pulse voltage is 600 V, the pulse frequency is 300 Hz, the negative bias voltage is 400 V, the ion source power is 300 W, and the deposition is carried out for 2 hours. A 1.1 μm ZrAlCuN coating is deposited. After cooling to room temperature, it is taken out and subjected to wet micro-sandblasting treatment. Spherical white corundum with a particle size of 40 μm is used and mixed with water for micro-sandblasting for 4-6 seconds. The micro-sandblasting pressure is 0.4 MPa to complete the surface modification of the cutting tool.
[0053] Among them, in step S1, the specific steps of cleaning the tool substrate are:
[0054] S11, ultrasonically cleaning the tool substrate, then rinsing it with tap water and deionized water, then activating it in 1wt% hydrochloric acid for 3 minutes, rinsing it with deionized water, ultrasonically cleaning it in acetone for 20 minutes, and drying it;
[0055] S12, placing the dried tool substrate under vacuum conditions and heating it to 400° C., introducing argon gas until the vacuum degree is 2 Pa, turning on the bias power supply to 1200 V, and performing argon ion sputtering cleaning;
[0056] S13. Argon gas is introduced into the tool substrate after argon ion sputtering cleaning until the vacuum degree is 0.7 Pa, the power is 400 W, and the ion source is turned on for cleaning for 20 minutes to obtain the cleaned tool substrate.
[0057] Comparative Example 1
[0058] The difference between Comparative Example 1 and Example 2 is that Comparative Document 1 does not perform dry micro-sandblasting.
[0059] Comparative Example 2
[0060] The difference between Comparative Example 2 and Example 2 is that Comparative Example 2 does not undergo wet micro-sandblasting.
[0061] Comparative Example 3
[0062] The difference between Comparative Example 3 and Example 2 is that in Comparative Document 3, a TiSiN coating is deposited on the TiN coating.
[0063] The cutting tools of Examples 1-3 and Comparative Examples 1-3 after surface modification were subjected to milling experiments, and the service life and wear amount of each cutting tool were measured respectively. The results are shown in Table 1.
[0064] Cutting test conditions: Machining method: external cylindrical intermittent turning; Cooling method: none; Cutting speed: Vc=250m / min; Cutting depth: ap=1mm; Cutting feed: f=0.2mm / rev; Cutting width: 50mm.
[0065] Table 1 Statistics of milling experiment results
[0066]
[0067]
[0068] It can be seen from Table 1 that the service life and wear resistance of the cutting tool after surface modification treatment of the present invention are significantly better than those of the comparative example, indicating that micro-sandblasting treatment plays an important role in improving the bonding strength between the cutting tool coatings and improving the coating roughness. The use of the Er element in the TiSiErN coating also plays a significant role in improving the overall performance, prolonging the service life and obtaining better comprehensive performance.
[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for surface modification of a cutting tool, characterized in that: The following steps are included in sequence: S1, depositing a TiN coating on the surface of the cleaned tool substrate by a multi-arc ion plating device; S2. Depositing a TiSiErN coating on the TiN coating; when depositing the TiSiErN coating, a SiTi target containing 0.5-3wt% Er is used, the mass ratio of Si to Ti is 1:4, the pressure is 2-4Pa, the nitrogen flow rate is 80-100mL / min, and the arc current is 100-120A; S3, after the TiSiErN coating is subjected to dry micro-sandblasting treatment, a mixed gas of argon and nitrogen is introduced into the magnetron sputtering equipment to a vacuum degree of 0.6-0.8 Pa, the ZrAlCu alloy target is turned on, the ZrAlCuN coating is deposited, and the coating is taken out after cooling to room temperature, and wet micro-sandblasting treatment is performed to complete the surface modification of the cutting tool; During dry micro-sandblasting, irregular white corundum with a particle size of 20-40 μm is used for micro-sandblasting through compressed air for 2-8 seconds, and the micro-sandblasting pressure is 0.1-0.3 MPa; when depositing the ZrAlCuN coating, the pulse voltage is 200-600V, the pulse frequency is 100-300Hz, the negative bias voltage is 300-400V, the ion source power is 200-300W, and the deposition is 1-2 hours; during wet micro-sandblasting, spherical white corundum with a particle size of 20-40 μm is mixed with water and micro-sandblasted for 4-6 seconds, and the micro-sandblasting pressure is 0.2-0.4 MPa; in the ZrAlCu alloy target, the Al atomic percentage does not exceed 15%, and the Cu atomic percentage does not exceed 2%.
2. The surface modification method of a cutting tool according to claim 1, characterized in that: In step S1, the specific steps of cleaning the tool substrate are: S11, ultrasonically clean the tool substrate, rinse it with tap water and deionized water, then place it in 1wt% hydrochloric acid for activation for 2-3 minutes, rinse it with deionized water, place it in acetone for ultrasonic cleaning for 18-20 minutes, and dry it; S12, placing the dried tool substrate under vacuum conditions and heating it to 200-400° C., introducing argon gas until the vacuum degree is 1-2 Pa, turning on the bias power supply to 1000-1200 V, and performing argon ion sputtering cleaning; S13. After the tool substrate is cleaned by argon ion sputtering, argon gas is introduced again until the vacuum degree is 0.4-0.7 Pa, the power is 350-400 W, and the ion source is turned on for cleaning for 10-20 minutes to obtain the cleaned tool substrate.
3. The surface modification method of a cutting tool according to claim 1, characterized in that: In step S1, when depositing the TiN coating, the pressure is 2-4 Pa, the nitrogen flow rate is 80-100 mL / min, and the arc current is 100-120 A.
4. The surface modification method of a cutting tool according to claim 1, characterized in that: The thickness of the TiN coating is 0.2-0.4 μm, the thickness of the TiSiErN coating is 0.5-0.9 μm, and the thickness of the ZrAlCuN coating is 1-1.8 μm.
5. The surface modification method of a cutting tool according to claim 1, characterized in that: In step S3, the nitrogen partial pressure in the mixed gas is 0.01-0.1 Pa.
Citation Information
Patent Citations
Hard and tough nano composite ZrAlCuN coating and preparation method thereof
CN104480443A
Preparation technology of compound PVC coating layer applied to high-speed cutting tool
CN109207924A